Die ontwikkeling van 'n vaste brandstof vuurpylmotor mondstuk - Le Roux, M. J.(Marthinus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ing.) -- Universiteit van Stellenbosch, 1993.